Clinical and Histopathological response to multidrug therapy in paucibacillary leprosy at the end of 6 Months: A prospective observational study from eastern India - Indrashis Podder; Abanti Saha; Debabrata Bandyopadhyay (Wolters Kluwer Medknow Publications, 2018)
Background: At present, the WHO recommends fixed duration multidrug therapy (FD-MDT) for the treatment of leprosy, in which treatment is provided for a fixed duration regardless of clearance of skin lesions or bacterial status of the patient. There is divided opinion regarding the efficacy of FD-MDT; especially for paucibacillary Hansen's disease, in which treatment is provided for 6 months. In addition, there is a paucity of literature on clinical and histopathological features of treated leprosy. Objectives: The objectives of this study were to prospectively observe the effects of MDT on clinical and histopathological features in paucibacillary leprosy and to assess the efficacy, safety and tolerability of MDT-paucibacillary (PB) regimen. Materials and Methods: A total of 52 new cases of PB leprosy diagnosed by clinicopathological correlation and slit skin smear were administered standard WHO PB-MDT for 6 months. Patients were reviewed at 3rd month and 6th month of therapy and 3 months posttherapy for their clinical and histopathological assessment. Results: Among 52 new cases of PB-leprosy 43 patients (mean age 31.74 ± 12.2 years, m:f 1.53:1) completed the study as per protocol. Fourteen percent patients recovered completely, 76.7% patients had a residual patch at the end. Number of lesions reduced significantly 2nd follow-up onwards while the lesional size showed significant decrease 1st follow-up onward. Nerve palpability also reduced significantly at treatment completion. Histological improvement was appreciable; lymphocytic infiltration reduced significantly 2nd follow-up onward and presence of granuloma 1st FU onward. Only four patients complained of occasional, uneventful epigastric pain during the study. Conclusion: Although the frequency of persistence of lesions after completion of therapy was high, histological evidence of activity was present in a minority (7%). Thus, the standard WHO MDT-PB regimen was found to be effective, safe and well-tolerated.